Age, tissue, genotype and virus infection regulate Wolbachia levels in Drosophila. Issue 11 (26th May 2020) - Kaur, Rupinder; Martinez, Julien; Rota‐Stabelli, Omar; Jiggins, Francis M.; Miller, Wolfgang J.
Abstract: The bacterial symbiont Wolbachia can protect insects against viral pathogens, and the varying levels of antiviral protection are correlated with the endosymbiont load within the insects. To understand why Wolbachia strains differ in their antiviral effects, we investigated the factors controlling Wolbachia density in five closely related strains in their natural Drosophila hosts. We found that Wolbachia density varied greatly across different tissues and between flies of different ages, and these effects depended on the host–symbiont association. Some endosymbionts maintained largely stable densities as flies aged while others increased, and these effects in turn depended on the tissue being examined. Measuring Wolbachia rRNA levels in response to viral infection, we found that viral infection itself also altered Wolbachia levels, with Flock House virus causing substantial reductions in symbiont loads late in the infection. This effect, however, was virus‐specific as Drosophila C virus had little impact on Wolbachia in all of the five host systems. Because viruses have strong tissue tropisms and antiviral protection is thought to be cell‐autonomous, these effects are likely to affect the virus‐blocking phenomenon. However, we were unable to find any evidence of a correlation between Wolbachia and viral titres within the same tissues. We conclude that Wolbachia levels within flies are regulated in a complex host–symbiont–virus‐dependent manner and this trinity is likely to influence the antiviral effects of Wolbachia .